Poezja K. I. Gałczyńskiego w edukacji młodzieży szkolnej = K. I. Gałczyński's Poetry in the Education of School Children - Łojek, Mieczysław (1930-2015) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article contains three thematical ranges. In the first range we see the not very friendly attitude of the literary reviewers towards Gałczyński's production after 1945, the second range shows the writer's admittance into curriculums and text-books after 1953, the last range informs about the increasing knowledge of biography and works as well.
Keywords: Gałczyński, Konstanty Ildefons (1905-1953); edukacja; młodzież